The histopathological profile of breast tumours at HTAA - Aung, Gyi (Kulliyyah of Medicine, 2015)
An overall perspective of the frequency of various breast problems can be gained from analyzing a large series of patients with breast symptoms who are seen at a health maintenance organization and women undergoing diagnostic breast biopsies. Three general points can be made. First, breast symptoms and signs are common problems in clinical practice. Second, it is fortunate that the majority of breast symptoms or lesions will prove to have a benign aetiology. Finally, the physical, psychological , and financial coasts of investigating benign breast disease, primarily to exclude malignancy, are substantial. Total number of 67 patients who were admitted to HTAA for the complaint of breast lump were studied. The surgeons took the biopsies and sent to the laboratory. Immunohistochemistry method is used to detect the receptors in the nucleus. ER and HER 2 markers are used. Some patients showed positive results in both markers but majority showed negative results. The evaluation of hormone receptors is most valuable to predict response to therapy. The group of patients who showed positive results had good response to therapy and had good prognosis.The group of patients who showed negative results had poor response to therapy and had poor prognosis. These results are useful for the clinicians when they plan to treat future patients with different therapeutic modalities.